(untitled) (Research, Society and Development, 2021)
The objective of this work is to understand the effectiveness of psychological counseling in bereaved individuals for the elaboration of mourning. There are specific objectives: to define the phenomenon of mourning and the counseling process; delineate the compromising elements of the elaboration of the mourning; and describe counseling as a strategy for preventing complicated grief. This is a narrative review, for which research was selected in the Scielo, VHL, Bireme, Pepsic, Lilacs and Google Scholar databases, using articles, books and theses on the proposed theme. As a result, the understanding of death was reached from different points of view. Psychological counseling and its effectiveness in the plurality of individuals have as a starting point to understand the suffering of the mourner. Authors like Kübler-Ross, John Bowlby and William Worden created the stages and tasks of mourning and described steps in this process that the individual can go through. Thus, there are therapeutic approaches, which help in coping with the state of complicated mourning, such as Gestalt, Psychoanalysis and Cognitive Behavioral Therapy. It was concluded that the importance of psychological counseling and therapeutic interventions is clear in mitigating the suffering of the bereaved individual. The theme of death and grief has its complexities, and studying this phenomenon allows us to understand the situation as a whole, which reveals the importance of this study.